Statistics at square two : understanding modern statistical applications in medicine - Campbell, Michael J., 1950-; Jacques, Richard M.; Ohio Library and Information Network (Hoboken : John Wiley & Sons, 2023)
"In the sixteen years since the second edition of Statistics at Square Two was published, there have been many developments in statistical methodology and in methods of presenting statistics. MJC is pleased that his colleague Richard Jacques, who has considerable experience in more advanced statistical methods and teaching medical statistics to non- statisticians, has joined him as a co-author. Most of the examples have been updated and two new chapters have been added on meta-analysis and on time series analysis. In addition, reference is made to the many checklists which have appeared since the last edition to enable better reporting of research. This book is intended to build on the latest edition of Statistics at Square One."--
Frontmatter -- Models, Tests and Data -- Multiple Linear Regression -- Multiple Logistic Regression -- Survival Analysis -- Random Effects Models -- Poisson and Ordinal Regression -- Meta-analysis -- Time Series Regression -- Exponentials and Logarithms -- Maximum Likelihood and Significance Tests -- Bootstrapping and Variance Robust Standard Errors -- Bayesian Methods -- R codes -- Answers to Exercises -- Glossary -- Index
Keywords: Medical statistics -- Data processing; Medical statistics -- Computer programs; Electronic books